Estudo in vitro de cito e fototoxicidade das drogas nitroheterocíclicas Nitracrina e Quinifuryl - Rossa, Marcelo Muniz (2005)
The cytotoxicity of two nitroheterocyclic compounds, Polish antitumor agent, Nitracrine and Russian antiseptic, Quinifuryl, towards three lines of cells were determined under normoxia conditions. Special emphasis has been placed on the comparisons of the drugs effects in highly tumorogenic, leukaemic P388 and K562 and non-tumorogenic, fibroblast cells NIH3T3. Both drugs showed significant cytotoxicity to all cell lines. Toxicity of both drugs toward murine leukaemia was substantially higher, compared to non-transformed murine fibroblasts. At the drug concentrations of 2 nmol/ml, it took 2-3 times less time to reach the LC50 with P388 compared to NIH3T3. Uptake of drugs by human erythroleukaemia cells was observed starting 10 min from the addition of the drug, while the LC50 values were achieved after 3 hr of incubation. This delay in cell killing may be due to the intracellular transformation of drugs required for cell killing. It was also investigated the cellular phototoxicity of both drugs towards murine leukaemia, fibroblast and human erythroleukaemia cells. The cytotoxicity of these drugs towards two lines of leukaemic cells and a line of non-transformed cells, was measured in comparison, on the dark and under illumination. Both drugs showed highly elevated cytotoxicity when illuminated with LC50 values 7-35 times lower after 1 h illumination compared to 1 h incubation of cells incubation with drug on the dark. Cytotoxicity of Nitracrine toward all cell lines studied exceeded that of Quinifuryl, both on the dark and under illumination, so that 10 times lower concentration of former drug was needed to reach the same toxicity as the latter. General toxic effect was calculated as a direct cell kill and a cell proliferation arrest. Micelles (PEG-2000-stearate) and small unilamellar liposomes (DSPC) were chosen as vehicles and cytotoxicity of free and immobilized drugs was studied. We show that both drugs are effectively immobilized and strongly retained by both micelles and unilamellar liposomes. Both drugs are highly toxic against all line cells, when is immobilized in liposomes DSPC. A protective effect of micelles against Nitracrine toxicity toward P388 cells was observed at low drug concentration (0.2 nmol/ml), but not at higher concentration (2 nmol/ml). Micelles also protected P388 cells against cytotoxicity of Quinifuryl.